2017
DOI: 10.3389/fmicb.2017.02168
|View full text |Cite
|
Sign up to set email alerts
|

More Than Gliding: Involvement of GldD and GldG in the Virulence of Flavobacterium psychrophilum

Abstract: A fascinating characteristic of most members of the genus Flavobacterium is their ability to move over surfaces by gliding motility. Flavobacterium psychrophilum, an important pathogen of farmed salmonids worldwide, contains in its genome the 19 gld and spr genes shown to be required for gliding or spreading in Flavobacterium johnsoniae; however, their relative role in its lifestyle remains unknown. In order to address this issue, two spreading deficient mutants were produced as part of a Tn4351 mutant library… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 81 publications
4
47
1
Order By: Relevance
“…Immersion challenge with F. psychrophilum probably reflects natural infection of rainbow trout better than injection. Thus, we developed a reproducible immersion challenge that does not involve preliminary stress [ 39 ] and used it to investigate the genetic variation of trout resistance to F. psychrophilum . Compared to injection challenge, immersion challenge may reveal QTL that drive defence mechanisms associated either with the entry of the bacterium into the host or with the host response once the pathogen has entered via the “natural” route, expanding the possibility of investigation of host antibacterial response.…”
Section: Introductionmentioning
confidence: 99%
“…Immersion challenge with F. psychrophilum probably reflects natural infection of rainbow trout better than injection. Thus, we developed a reproducible immersion challenge that does not involve preliminary stress [ 39 ] and used it to investigate the genetic variation of trout resistance to F. psychrophilum . Compared to injection challenge, immersion challenge may reveal QTL that drive defence mechanisms associated either with the entry of the bacterium into the host or with the host response once the pathogen has entered via the “natural” route, expanding the possibility of investigation of host antibacterial response.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the improved protection of bacteria in biofilm growth mode is usually accompanied by enhanced virulence and pathogenicity (He and Ahn, 2011 ; Flemming et al, 2016 ). However, there are few studies on F. psychrophilum comparing free-living vs. biofilm lifestyles (e.g., De la Fuente et al, 2013 ), and research based on mutants with defects in motility (Álvarez et al, 2006 ; Pérez-Pascual et al, 2015 ) has reported an attenuation of virulence in spread-deficient mutants compared to wild-type strains (Pérez-Pascual et al, 2017 ). These findings suggest that F. psychrophilum biofilm cells could be less virulent than motile free-living cells; however, this suggestion overlooks the fact that F. psychrophilum infections rely on initial attachment to mucosal external surfaces of fish (Papadopoulou et al, 2017 ) for cell colonization and long-term persistence of adhered cells.…”
Section: Discussionmentioning
confidence: 99%
“…Ostland and colleagues previously demonstrated that when a crude extracellular preparation of F. psychrophilum was injected directly into the muscle of rainbow trout, muscle necrosis was observed [ 246 ]. This led to further studies attempting to determine virulence factors of F. psychrophilum , including the identification of extracellular proteases and mutation analyses using the identified secreted proteases [ 247 , 248 , 249 , 250 ]. Unfortunately, identification of individual virulence factors has had limited success, but loss of virulence has been observed in some cases [ 247 , 251 ].…”
Section: Current Methods Of Bacterial Disease Prevention In Aquacumentioning
confidence: 99%
“…This led to further studies attempting to determine virulence factors of F. psychrophilum , including the identification of extracellular proteases and mutation analyses using the identified secreted proteases [ 247 , 248 , 249 , 250 ]. Unfortunately, identification of individual virulence factors has had limited success, but loss of virulence has been observed in some cases [ 247 , 251 ]. Removal of predicted virulence factors can result in a decrease in virulence for aquatic bacterial pathogens in vitro [ 252 , 253 , 254 ], but this is not always the case [ 255 , 256 ].…”
Section: Current Methods Of Bacterial Disease Prevention In Aquacumentioning
confidence: 99%